Fingerprint recognition system : (prepocessing) - Norzaliza, Bidin (2005)
Fingerprint recognition system was implementing for a long time in security system.Fingerprint is one of step to recognize the identity of person beside from signature because each person has a unique thumbprint although twin borne.The utilizing of this system is to enhance the security system in server room KUKTEM and only the authorized person will able to enter the room. This project develop prototype in concentrating on the preprocessing activities which are image acquisition, threshold and thinning.The objective of this project is to make a comparison between mean value and median value of threshold and make comparison between one pass and two pass algorithm of thinning.The prototype will only use 50 pieces gray scale JPEG image with the size of 240 x 240 pixels. The prototype will develop in the next chapter and the results will be discussed in the end of chapter.